SEMINAL CHARACTERISTICS AND THEIR INTERRELATIONSHIPS IN GIR BULLS - VALA, S B; VALA, K B; SOLANKI, G B; PADODARA, R J; PARMAR, K H (The Indian Journal of Animal Reproduction, 2021)
The present investigation was undertaken on semen quality parameters and their interrelationships on three Gir bulls (5 years old) maintained at Cattle Breeding Farm, Junagadh. Semen ejaculates (n=30, 10/bull) were collected using artificial vagina (Danish model) once weekly and were soon evaluated for physico-morphological attributes. The ejaculate volume, sperm concentration, mass motility (0-5 scale), individual sperm motility, sperm viability, sperm abnormality, HOST reactive spermatozoa, and acrosome integrity were found to be 7.93±1.72 ml, 1376.90±55.21 million/ml, 3.70±0.08, 83.67±0.93 %, 87.03±0.74 %, 9.87±0.52 %, 90.17±0.47 % and 75.30 ±1.07 %, respectively. There was a significant (P<0.01) difference only in ejaculate volume and sperm concentration between bulls. The sperm concentration, sperm motility, viability, acrosome integrity and plasma membrane integrity were highly significantly and positively (r= 0.512 to 0.880; P<0.01) interrelated and all of them had significant negative correlations with sperm abnormality (r= -0.498 to -0.827). The ejaculate volume did not show significant correlations with any of the other traits studied. The semen quality in general was within normal physiological limits of the breed.